2022
DOI: 10.1039/d2np00047d
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbiaditerpenoids: isolation, structure, bioactivity, biosynthesis, and synthesis (2013–2021)

Abstract: This review covers the recent progress on the isolation, identification, bioactivity, biosynthesis, and total synthesis of Euphorbia diterpenoids from 2013 to 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 377 publications
0
42
0
Order By: Relevance
“…Generally, diterpenoids are recognized as the characteristic metabolites of the Euphorbiaceae plants [ 37 ]. Interestingly, previous and current chemical investigation suggested that triterpenoids were the main metabolites of G. puberum .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, diterpenoids are recognized as the characteristic metabolites of the Euphorbiaceae plants [ 37 ]. Interestingly, previous and current chemical investigation suggested that triterpenoids were the main metabolites of G. puberum .…”
Section: Discussionmentioning
confidence: 99%
“…The intramolecular cyclization and/or rearrangement serves as a prevailing method for constructing skeletally diverse polycyclic diterpenoids derived from jatrophanes. Among them, 1,2-rearrangement was most adopted method, as exemplified by pepluanes [9(10→19)- abeo -jatrophane], euphosalicin [11(10→19)- abeo -jatrophane], and 1(15→14)- abeo -jatrophane. , In the study presented here, the 1,2-rearrangement of C-9 from C-10 to C-18 in jatrophane formed the C-9–C-18 linkage in euphylonoid A ( 1 ) while the migration of C-14 from C-13 to C-20 generated the C-14–C-20 linkage in euphylonoid B ( 2 ). The latter represents the first example of such an arrangement in jatrophanes.…”
mentioning
confidence: 92%
“…Jatrophanes make up a group of chemotaxonomically significant macrocyclic diterpenoids from plants of the Euphorbiaceae family . Structurally, they feature a trans -bicyclo­[10.3.0]­pentadecane core with a gem -dimethyl at C-10 and three methyls at C-2, C-6, and C-13.…”
mentioning
confidence: 99%
“…A tigliane diterpenoid from E. semiperfoliata , 4α deoxyphorbol‐12‐tiglate‐13‐isobutyrate, has been shown to selectively inhibit HIV replication at nanomolar concentrations by downregulating CD4, CXCR4, and CCR5 and to reactivate HIV in resting peripheral blood mononuclear cells (PBMCs) by activating PKCq/MEK and NF‐kB. Additionally, it demonstrated considerable synergism with other HIV inhibitors and latency reversal medications (LRAs) [13] . The Epstein‐Barr virus was inhibited by the euphominoid B, ent ‐rosane diterpenoid isolated from E. milii , with an EC 50 of 5.4 μM, which is equivalent to the EC 50 of (+)‐rutamarin, the positive control [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it demonstrated considerable synergism with other HIV inhibitors and latency reversal medications (LRAs). [13] The Epstein-Barr virus was inhibited by the euphominoid B, ent-rosane diterpenoid isolated from E. milii, with an EC 50 of 5.4 μM, which is equivalent to the EC 50 of (+)-rutamarin, the positive control. [14] The bioactivities of a set of jatrophanes were assessed against the chikungunya virus (CHIKV), where compound 3,5,7,15-tetraacetoxy-2-hydroxy-8-tigloyloxy-9,14-dioxojatropha-6(17),11Ediene had higher potency (EC 50 = 0.76 μM) and a larger selective index (SI = 208) than the positive control drug chloroquine (EC 50 = 10 μM; SI = 8.9).…”
Section: Introductionmentioning
confidence: 99%